Pengaruh Perputaran Kas, Perputaran Piutang Dan Perputaran Persediaan Terhadap Profitabilitas Pada Perusahaan Pertambangan Yang Terdaftar Di Bursa Efek Indonesia Periode 2017-2019 - Septi Oktarina; Leriza Desitama Anggraini; Rafika Sari (Training & Research Institute - Jeramba Ilmu Sukses, 2022)
The objective of this research is to observe the significant effect of cash turnover, accounts receivable turnover and inventory turnover on profitability. This research was conducted at mining companies on the Indonesia Stock Exchange on the year of 2017 until 2019 which amounted to 14 companies as samples that fit the criteria. The sampling technique used was purposive sampling technique. Data were obtained by literature study and documentation. The data analysis method used was multiple linear regression analysis. The results of the research on the T test shows that cash turnover has no effect on the profitability (ROA) of mining companies listed on the IDX for the 2017-2019 period. Accounts receivable turnover has a negative and significant effect on the profitability (ROA). Inventory turnover has a positive and significant impact on the profitability (ROA). Overall, the results of the research on the F test show that cash turnover, accounts receivable turnover and inventory turnover have a simultaneous effect on profitability.